Strategi Pengembangan Sekolah Berbasis Kelapa Di Indragiri Hilir - Candra Sari Mutiara; Gevisioner (Jurnal Kebijakan Pembangunan dan Inovasi, 2017)
The development of human resources to optimize the utilization of regional superior potential can be done through education based on local and global advantages. The purpose of this research is to formulate the strategy of development of coconut-based SMK in Indragiri Hilir. The results showed that Indragiri Hilir Regency requires graduates of SMK who have competency in the field of empowering coconut plant. While the District of Indragiri Hilir require graduates of vocational schools who have competence in the field of expertise in coconut plant empowerment. The development strategy of coconut-based SMK in Indragiri Hilir Regency uses the pattern of integration into art and culture subjects, local content, and technological science subjects.